Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1191/026921501672063235
|View full text |Cite
|
Sign up to set email alerts
|

A randomized efficacy and feasibility study of imagery in acute stroke

Abstract: Imagery is a clinically feasible, cost-effective complement to therapy that may improve outcomes more than participation in therapy only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
239
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(248 citation statements)
references
References 24 publications
4
239
0
4
Order By: Relevance
“…One study compared conventional physiotherapy and physiotherapy plus motor imagery in subacute with chronic stroke patients and demonstrated a greater improvement of hand function with the additional mental practice. 44 Performance improvements demonstrated with motor imagery alone after chronic stroke, as expected, were more modest than those identified with physical training.…”
Section: Mental Practicesupporting
confidence: 57%
“…One study compared conventional physiotherapy and physiotherapy plus motor imagery in subacute with chronic stroke patients and demonstrated a greater improvement of hand function with the additional mental practice. 44 Performance improvements demonstrated with motor imagery alone after chronic stroke, as expected, were more modest than those identified with physical training.…”
Section: Mental Practicesupporting
confidence: 57%
“…Alden, Dale, & DeGood, 2001;Gregerson, Roberts, & Amiri, 1996;Page, Levine, Sisto, & Johnston, 2001;Simonton, Simonton, & Creighton, 1984;Vines, 1988), but has not been extensively investigated in the area of sport-injury rehabilitation. The injured athletes in the present study reported the use of healing imagery to aid in the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…66 The MAL is an upper-extremity disability measure (self-report interview). The MAL 67,68 is a semi-structured interview during which participants are asked to rate how much and how well (6-point scale; range, 0 [worst] to 5 [best]) they use their more affected arm for 30 ADL items in the home environment over a specified period. Mental imagery was assessed using 3 measures.…”
Section: Methodsmentioning
confidence: 99%